1998
DOI: 10.1002/jmri.1880080527
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional triple‐quantum‐filtered 23Na imaging of the dog head in vivo

Abstract: Multiple-quantum (MQ) -filtered 23Na NMR has been proposed as a means to partially discriminate between intracellular and extracellular sodium. However, low signal-to-noise ratio (SNR) has been a major obstacle to MQ-filtered 23Na imaging becoming an important technique for biological and clinical applications. We compared the various MQ-filtered 23Na imaging pulse sequences to select the optimum sequence that provides the best SNR. The results of phantom experiments show that the gradient-echo MQ-filtered 23N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The 23 Na signal in brain tissue exhibits biexponential transverse (T2) relaxation with fast and slow relaxing components in which fractions may also change with disease (25). The fast-relaxing component contributes up to 60% of the signal with a T2 in the range of 0.5-5.0 msec, depending on tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…The 23 Na signal in brain tissue exhibits biexponential transverse (T2) relaxation with fast and slow relaxing components in which fractions may also change with disease (25). The fast-relaxing component contributes up to 60% of the signal with a T2 in the range of 0.5-5.0 msec, depending on tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…One of the motivations for pursuing triple‐quantum‐filtered (TQF) sodium NMR (1) in cerebral ischemia, or any other neurological disorder, is the potential to selectively measure intracellular sodium changes, which could be a direct marker of compromised ionic homeostasis. Stroke model studies (2, 3) have shown much larger changes in the ischemic lesion relative to the nonaffected hemisphere for TQF NMR than for single‐quantum (SQ) NMR, consistent with a sodium shift to intracellular space following anoxic depolarization. TQF sodium NMR has also shown signal increases in animal models of tumors (4–6).…”
Section: Introductionmentioning
confidence: 89%
“…This approach is a major departure from that used previously in small bore systems (10,15), where the use of refocusing pulses was advocated as a means to reduce signal loss due to main magnetic field inhomogeneities. The use of this approach is justified by the fact that over a large (Ͼ15 cm) field of view (FOV), the signal loss due to inhomogeneous RF excitation typically exceeds that arising because of main magnetic field inhomogeneities (13).…”
Section: Introductionmentioning
confidence: 97%